Investigating the dietary intentions of Iranian tourists regarding the consumption of local food - Mohammadian Pouri, Maryam; Rahimian, Mehdi; Gholamrezai, Saeed (Frontiers in Nutrition, 2023)
Many studies have been conducted about the different aspects of tourists' food. Tourist food behaviors and intentions are decisive components in travel. Limited studies to analyze tourists' preference for local foods led us to help fill the research gap in this field by conducting this research. This study aims to use the extended theory of planned behavior (TPB) by adding risk perception (RP) to investigate the tourists' intentions towards local food (TILF) in Iran. The developed model tested 313 tourists visiting local food supplies. Results show that the extended TPB explains 87.8% of tourist intention variance. Three variables of the original TPB had positive impacts on tourists’ intentions. A notable result of this study was the realization of a negative relationship between RP and TILF. This research has provided recommendations to strengthen tourists' intentions toward local foods by influencing their attitudes, mental beliefs, perceived behavioral control, and risk perception.